2016
DOI: 10.1002/eji.201646421
|View full text |Cite
|
Sign up to set email alerts
|

Increased Th2 activity and diminished skin barrier function cooperate in allergic skin inflammation

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease induced by a complex interaction between susceptibility genes encoding skin barrier components and environmental allergen exposure that results in type 2 cytokine production. Although genetic lesions in either component can be risk factors for disease in patients, whether these pathways interact in the development of AD is not clear. To test this, we mated mice with T-cell specific expression of constitutively active Stat6 (Stat6VT) that spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
0
28
1
Order By: Relevance
“…In addition, in human models it was found that both antimicrobial activity and skin barrier proteins are decreased in AD skin by Th2 in a Stat6-dependent manner [22,23]. Importantly, Sehra et al were unable to induce an AD-like phenotype in mice carrying the single FLG-mutation [26]. This seems in contrast with a previous publication in the same mouse strain, but in this study the AD-like phenotype was only observed in older mice [9].…”
Section: Interplay Between Systemic and Local Immune Responses In Adcontrasting
confidence: 76%
See 4 more Smart Citations
“…In addition, in human models it was found that both antimicrobial activity and skin barrier proteins are decreased in AD skin by Th2 in a Stat6-dependent manner [22,23]. Importantly, Sehra et al were unable to induce an AD-like phenotype in mice carrying the single FLG-mutation [26]. This seems in contrast with a previous publication in the same mouse strain, but in this study the AD-like phenotype was only observed in older mice [9].…”
Section: Interplay Between Systemic and Local Immune Responses In Adcontrasting
confidence: 76%
“…The publication of Sehra et al in the current issue of this journal now further elucidates the interaction between systemic and local changes that are crucial for the development of AD and the nature of the adaptive immune signals [26]. In their mouse model, they combined mutations in FLG in Flaky tail mice with a T-cellspecific expression of constitutively active Stat6.…”
Section: Interplay Between Systemic and Local Immune Responses In Admentioning
confidence: 99%
See 3 more Smart Citations